THE OPERARIADO INDUSTRIAL RESTRUCTURING IN THE CONTEXT OF PRODUCTIVE: A GREAT CHALLENGE OF THE UNION MOVEMENT IN THE 80S (THE TWENTIETH CENTURY) IN THE INDUSTRIAL POLE OF MANAUS - PIM - Milton Melo dos Reis Filho (Travessias, 2008)
This analysis focused on the theme entitled The working in the context of industrial restructuring Productive: a great challenge of the union movement in the 80s (the twentieth century) in the Industrial Pole of Manaus - PIM will help us better understand the role of trade unions in more cohesive and consistent in the process of change. It is known that from the XXI century advances in microelectronics technology and streamlining of the process of organizational techniques work passed to strengthen. It was visible in some employee reaction to the new model about to be deployed in different industries, where the economies of scale in production sought Fordist mass were replaced by a growing ability to manufacture a variety of goods in small lots. Accordingly, the weakening of the forces union on account of the new model of capitalist production called flexible specialization just inaugurating a precarious and the emergence of a new time in the world of work. In the 80s, specifically, workers workers were threatened by their immediate bosses and dismissed, simply. To consolidate this discussion, we believe that the work also involves different types of power on the raw materials, tools and machinery and, more important today, on their own people. Therefore it is essential that takes into consideration all aspects of the occupation - qualification, power, income and status - to understand the meaning of work and sources of satisfaction that it can offer. Translates is about the new flag of the Brazilian trade union movement.